THE EFFECT OF LABOR PREPARATION CLASSES WITH WHATSAPP GROUP (WAG) IN TRIMESTER III PREGNANT WOMEN TOWARDS ANXIETY IN DEALING WITH LABOR IN PMB MIDWIVES N BANDUNG CITY, 2020 - Iceu Mulyati (SEKOLAH TINGGI ILMU KESEHATAN (STIKes) INDRAMAYU, 2020)
The process of pregnancy is a long process. 9 months 10 days, many pregnant women are negligent and even do not make preparations for the delivery, due to the lack of preparation for labor, many pregnant women experience anxiety. Anxiety before childbirth is commonly experienced by mothers even though childbirth is a physiological thing, a way to relieve anxiety, worry, and anxiety, and increase self-confidence by looking for information. information, the use of technology is used in this study, namely the use of Whatapps Group as a medium of education. The purpose of this study is to see whether there is an effect of labor preparation classes on anxiety levels, the method used is the One-Group Pretest-Posttest Design of this study to measure the level of anxiety in mothers third trimester of pregnancy before and after. The results showed that the level of anxiety before 60% moderate anxiety level and after 43.3% did not experience anxiety, from the results of the Wilxocon test with a p-value of 0.000 showed an effect, it can be concluded that the use of Whatapps Group in implementing classes for pregnant women has a quite positive impact on pregnant women in the face of childbirth.